2004
DOI: 10.1063/1.1823012
|View full text |Cite
|
Sign up to set email alerts
|

1.3 μ m  InGaAs vertical-cavity surface-emitting lasers with mode filter for single mode operation

Abstract: We report on the performance and analysis of 1.3μm range InGaAs∕GaAs vertical-cavity surface-emitting lasers (VCSELs) with an integrated mode filter consisting of a patterned silicon layer on the top distributer Bragg reflector. In this way, 1mW of single mode power is obtained from a device with a wavelength of 1265nm and a threshold current of 2.6mA at room temperature. An effective index model is used to extract the internal and external losses of the VCSEL structure and to predict the modal losses with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The numerical model was also used to analyse the modal losses of the fundamental mode and the first higher order mode of the device. This analysis is presented in [26]. It was found that the modal losses differ only by approximately 2% which explains the multimode operation.…”
Section: Single Mode Operationmentioning
confidence: 95%
“…The numerical model was also used to analyse the modal losses of the fundamental mode and the first higher order mode of the device. This analysis is presented in [26]. It was found that the modal losses differ only by approximately 2% which explains the multimode operation.…”
Section: Single Mode Operationmentioning
confidence: 95%
“…The dilute-nitride materials are full of potential in this area, but the growth of these nitrogen-containing materials is quite challenging and the reliability of this novel material is still questionable. Therefore, the mature InGaAs/GaAs QWs seem to be a candidate for 1.2-1.3 mm lasers and they have been re-visited by the scientific community [7][8][9][10][11][12][13][14][15][16][17][18][19], with results such as the MBEgrown 1.24 mm lasers reported by Sung and Lin [7] and the metalorganic vapor-phase epitaxy (MOVPE)-grown 1.26 mm VCSELs reported by Chen et al [8].…”
Section: Introductionmentioning
confidence: 90%
“…It requires much effort to optimize the growth conditions of highly strained InGaAs layers. However, with the advancing state-of-the-art epitaxial techniques, several groups [7][8][9][10][11][12][13][14][15][16][17][18][19] have reported InGaAs/GaAs QWs operating around 1.2 mm. The InGaAs/ GaAs QWs have the potential to be low-cost and high-performance semiconductor lasers, especially for the high-power 1.2 mm edge-emitting lasers [9] and 1.3 mm vertical cavity surface emitting lasers (VCSELs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that, rather than etching a surface relief, a relief structure can be deposited to preferentially lower the cavity loss for the fundamental mode [64,65].…”
Section: Single-mode Emission From Inherently Multimode Vcselsmentioning
confidence: 99%